A compact dual-band reconfigurable antenna with metamaterial for IoT applications - Abdullah Hasan Ali; Jamal Mohammed Rasool; Ali Kadhum Abd; Md. Shabiul Islam; Mohamed Ouda; Mohamad A. Alawad; Mohammad Tariqul Islam (Scientific Reports)
Abstract This study presents a compact antenna designed for Internet of Things (IoT) applications, utilizing advanced wireless communication technologies. The antenna is designed to operate at dual frequencies (2.4 GHz and 6.04 GHz) with 12 multipath T-structured metamaterials. In Mode 1 (D1 OFF), the antenna operates at 2.4 GHz with a bandwidth of 80 MHz (2.36–2.44 GHz). In Mode 2 (D1 ON), it functions at 6.04 GHz with a bandwidth of 300 MHz (5.9–6.2 GHz). The design employs a commercially available FR-4 substrate with a relative permittivity of 4.3 and a loss tangent of 0.025, all within a compact size of (0.16λ₀ × 0.12λ₀ × 0.0112λ₀). The antenna radiator integrates a single PIN diode (SMP1340-079LF) along with a complete biasing circuit to achieve reconfigurability. The proposed design overcomes the conventional limitations by integrating T-structured metamaterials to achieve dual-band operation in a compact size. This antenna is ideal for wireless communication applications due to its manufacturability, enhanced gain, and low return loss. It is well suited for widely used frequency ranges, including Wi-Fi and Bluetooth. The results demonstrate that a miniaturized antenna with excellent efficiency has achieved, making it a promising solution for next-generation IoT devices.